pH-Responsive Nanostructures Based on Surface Active Fatty Acid-Protic Ionic Liquids for Imiquimod Delivery in Skin Cancer Topical Therapy - Tampucci, Silvia (Pharmaceutics, 2020)
For topical treatment of skin cancer, the design of pH-responsive nanocarriers able to selectively release the drug in the tumor acidic microenvironment represents a reliable option for targeted delivery. In this context, a series of newly synthesized surface-active fatty acid-protic ionic liquids (FA-PILs), based on tetramethylguanidinium cation and different natural hydrophobic fatty acid carboxylates, have been investigated with the aim of developing a pH-sensitive nanostructured drug delivery system for cutaneous administration in the skin cancer therapy. The capability of FA-PILs to arrange in micelles when combined with each other and with the non-ionic surfactant d-α-Tocopherol polyethylene glycol succinate (vitamin E TPGS) as well as their ability to solubilize imiquimod, an immuno-stimulant drug used for the treatment of skin cancerous lesions, have been demonstrated. The FA-PILs-TPGS mixed micelles showed pH-sensitivity, suggesting that the acidic environment of cancer cells can trigger nanostructures’ swelling and collapse with consequent rapid release of imiquimod and drug cytotoxic potential enhancement. The in vitro permeation/penetration study showed that the micellar formulation produced effective imiquimod concentrations into the skin exposed to acid environment, representing a potential efficacious and selective drug delivery system able to trigger the drug release in the tumor tissues, at lower and less irritating drug concentrations.